Wilhelm von Humboldt and ecolinguistics - Harden, Theo (2018)
The aim of the present article is to show that Wilhelm von Humboldt’s linguistic and philosophical works already contain traces of an approach which today is known as ecolinguistics and that this eminent thinker did indeed anticipate certain ideas which constitute this particular branch of language research. Humboldt always emphasised that linguistic research cannot be limited to structural issues, but that the true and ultimate goal of linguistics is to understand the spirit which is the driving force behind the languages and their speakers. For this reason, he substituted the Aristotelian model in which the differences between languages are seen as mere differences of sounds by one which identifies the latter on the level of worldviews (Weltansichten). Furthermore, Humboldt introduced a type of dialectics which is based on the complementary forces of the masculine and the feminine and he ties this notion to all human creative processes.